Coupling of a bimetallic strip heat engine with a piezoelectric transducer for thermal energy harvesting. (23rd March 2016) - Boughaleb, J.; Arnaud, A.; Monfray, S.; Cottinet, P.J.; Quenard, S.; Boeuf, F.; Guyomar, D.; Skotnicki, T.
ABSTRACT: The field of energy harvesting became attractive due to the development of wireless sensors networks. Consequently many systems emerged to harvest wasted energies to convert it into usable electrical energy. The goal behind these harvesters is to be able to supply low power sensor nodes. The research work described in this paper deals with a thermal energy harvester based on a double stage conversion to obtain usable electrical energy. More specifically, this paper presents the properties of the materials used in this harvester. It concerns its components, its thermal modeling and optimization, its electrical modeling and finally the piezoelectric benchmark.